2022
DOI: 10.3390/en15030932
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Programming of Airports by Identification of Non-Efficient Units

Abstract: This article concerns the identification of inefficient airports and the exploration of spatial autocorrelation for programming sustainable development. The first research question was: do domestic airports cooperate by shifting passenger service and traffic to the geographically closest airport to respect the idea of sustainable development (in view of the rationalization of energy consumption)? The second question was: do they excessively compete for passengers and the carriers serving them? The aim was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The result of our research is a possibility for creation the new concept of virtual air carrier business model, which could be established in Slovak republic and revives the Slovak air transport market after COVID-19 pandemic crisis. A lot of airlines especially after the COVID-19 crisis do not have a rationalized structure of inputs to results and strive to dominate the market as Szaruga and Załoga declared for the airports [54]. We can not prepare strategic decision without rationalization and definition of the priorities.…”
Section: Discussionmentioning
confidence: 99%
“…The result of our research is a possibility for creation the new concept of virtual air carrier business model, which could be established in Slovak republic and revives the Slovak air transport market after COVID-19 pandemic crisis. A lot of airlines especially after the COVID-19 crisis do not have a rationalized structure of inputs to results and strive to dominate the market as Szaruga and Załoga declared for the airports [54]. We can not prepare strategic decision without rationalization and definition of the priorities.…”
Section: Discussionmentioning
confidence: 99%
“…A green airport requires the green buildings and green practices, which involves in energy demands, air quality, water quality, noise, recycling and reuse of the materials and food. [36,37] At this part are described some green practices in the airports of Tampa, Seymour in Galapagos islands and Dallas Love Field Airport in Texas.…”
Section: Green Practices In Airportsmentioning
confidence: 99%
“…The research conducted by Preuss (2015) revealed that significant sustainable development effects can be achieved through organizing mega sport events by investing obtained funds in buildings and adapting the infrastructure for the event using renewable resources. Nowadays, companies focus on persuading consumers of their sustainability efforts through new CSR tactics (Vollero et al, 2016;Millington et al, 2021;Szaruga, Załoga, 2022). It is also essential that The UN's call to consider the fundamental societal changes required to stem the tide of climate change, and the importance of the environment in matters of development should resonate with critical scholars of sport.…”
Section: Literature Reviewmentioning
confidence: 99%